2020
DOI: 10.1186/s12913-020-05485-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the perceived barriers of health care access among reproductive-age women in Ethiopia: a secondary data analysis of 2016 Ethiopian demographic and health survey

Abstract: Background: Health care access is the timely use of personal health services to achieve the best health outcomes. Problems in accessing health care among reproductive-age may lead to various adverse health outcomes like death and disabilities. Therefore, this study aimed to identify factors associated with the perceived barriers of healthcare access among reproductive-age women in Ethiopia. Method: This study was based on secondary data sources from the 2016 Ethiopia Demography and Health Survey. The individua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
33
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 22 publications
14
33
2
Order By: Relevance
“…The predominant barriers were getting money needed for treatment and distance to health facility. This confirms a previous study in Ethiopia by Tessema and Kebede [ 17 ]. The study also showed that women aged 30–34 and 35–39 had lower odds of facing barriers in accessing healthcare, compared to those aged 45 and above.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The predominant barriers were getting money needed for treatment and distance to health facility. This confirms a previous study in Ethiopia by Tessema and Kebede [ 17 ]. The study also showed that women aged 30–34 and 35–39 had lower odds of facing barriers in accessing healthcare, compared to those aged 45 and above.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence in this study is similar to prevalence of healthcare accessibility barriers reported in South Africa (65%) [ 20 ], Rwanda (64%) [ 18 ], Ethiopia (69%) [ 17 ], and Tanzania (65%) [ 16 ]. The predominant barriers were getting money needed for treatment and distance to health facility.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations